Diagnostic Approach to Keratoacanthoma : Differentiating with Squamous Cell Carcinoma - Firda Fakhrena; A.A Ayu Adisti Nina Yuniandari; Rafdi Ahmed; Diana Wijayati (Jurnal Syntax Transformation, 2022)
Keratoacanthoma (KA) is a cutaneous neoplasms from the pilosebaseous unit, characterized as a rapidly growing tumor and usually show spontaneous regression. A major difficulty in dealing with these neoplasms is to differentiating them from squamous cell carcinoma, clinically and histologically. However, the change for regression has led keratoacanthoma as benign tumors with different pathophysiological mechanism from cutaneous squamous cell carcinoma (cSCC). The similarities between keratoacanthoma and cSCC, especially the well-differentiated variant cSCC, has led to the general recommendation for surgical excision of keratoacanthoma to make sure that a potentially malignant cSCC is not left untreated. Differentiating KA with cSCC would change management strategies to the less invasive treatment modalities, prevent surgical morbidity, and reduce healthcare costs. Methods : We searched for relevant journal articles in PubMed with a systematic search using PICO, with the keyword “Keratoacanthoma“ or “Squamous cell carcinoma“ and “Diagnostic“ or “History, physical examination, histology“. We got 825 publications and we filtered by the last five years and we generated 12 publications from 2017-2022 after we checked from the title and abstract for relevancy. Conclusion : The review revealed that keratoacanthoma can be distinguished from squamous cell carcinoma from the biological differences of spontaneous regression, very rapid growth and the absence of malignant features. It can also be distinguished by the histological and immunohistochemistry examination such as the presence of epithelial lips, neutrophilic microabscesses within the atypical epithelium, firm boundaries between tumor and stroma, ulceration, many mitotic cells and pleomorphic or anaplastic. The study also show that CD1a and Hsp60 can help distinguish between KA and SCC.